NON-STANDARD FORMS FOR CHECKING HOMEWORK IN THE RUSSIAN LANGUAGE (Western European Journal of Linguistics and Education, 2024)
This article examines non-standard forms of checking homework and provides methodological recommendations for Russian language teachers in non-linguistic universities. Working at home, students not only consolidate the knowledge acquired in class, improve skills and abilities, but also acquire the skills of independent work, cultivate organization, hard work, accuracy, and responsibility for the assigned work. In this case, checking homework plays a very important role. As a result of systematic checking of assignments, students receive the necessary advice and evaluation of completed assignments on time, which is very important in educational terms. The teacher can find out how deeply the material has been mastered and to what extent students are ready to acquire new knowledge